Covalent organic frameworks embedded in polystyrene membranes for ion sieving. Issue 35 (13th April 2022) - Niu, Bo; Xin, Weiwen; Qian, Yongchao; Kong, Xiang-Yu; Jiang, Lei; Wen, Liping
Abstract : A mixed matrix membrane composed of COF-300 and polystyrene (PS) with controllable thickness and porosity achieves ion sieving performance, which is dependent on the regular pore size and surface functional groups of COF-300. Abstract : A mixed matrix membrane composed of COF-300 and polystyrene (PS) with controllable thickness and porosity achieves ion sieving performance, which is dependent on the regular pore size and surface functional groups of COF-300. Hence, the selectivity of the COF-300/PS membrane for K + /Li + and Mg 2+ /Li + reached 31.5 and 14.7, respectively.